(untitled) (Current Problems in Rail Vehicles, 2021)
A relatively new trend in the management of the friction between the wheel and rail is the application of so-called friction modifiers or lubricants on top of the rail in order to optimise coefficient of adhesion. The aim of this paper is to present this issue and to demonstrate the possibilities of laboratory evaluation of performance parameters of top-of-rail lubricants and friction modifiers. Important implications for the prescription of their application are discussed.